Parents' knowledge of the sensory integrative approach within occupational therapy at a remedial school - Fingleson, Danielle Louise (My University, 2019)
Sensory integration has been used as an approach to treat children with various learning disabilities. The approach is used by occupational therapists as it follows a developmental sequence to assist children with sensory integrative difficulties to participate in their various occupations (1). Parents’ involvement in their children’s occupational therapy is seen as a fundamental part of the therapy process as they play a vital role in the carryover of therapy into the home environment. The purpose of the study was thus to describe parents’ knowledge of a sensory integrative approach in occupational therapy within a remedial school environment. A quantitative method was used, utilising a descriptive design that included the use of surveys. A specifically designed self-report questionnaire was distributed to parents, both in hard copy and electronic format, whose children receive the sensory integrative approach at a remedial school in Johannesburg. The required sample size that was identified for the research was 152 parents, including both mothers and fathers, however in the six-month data collection period, only 61 parents completed the questionnaire despite the researcher sending out the questionnaire multiple times. One of the parent questionnaires was excluded from the analysis of the results as the parent did not complete all the required demographic information, resulting in a sample size of 60 parents comprised of 53 mothers and 7 fathers. Six categories emerged out of the analysis on how parents perceive what the sensory integrative approach is. The majority (80%) of the parents had an understanding of what the sensory integrative approach is, however the remaining 20% had no understanding or an incorrect understanding. These results were also analysed using quantitative content analysis where preceptages and freqeucies were calculated to determine whether the findings support those seen in previous research. Parents perceived the approach to be both effective and beneficial to their children, and reported decreases in sensory defensive behaviours, anxiety and aggression, as well as increases in confidence, social skills and concentration. The information gathered in this study will be used to guide future therapy in the remedial school. The findings will also aid in workshop development for parents, as well as to ensure that collaborative goal setting is taking place in the therapy setting.
research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy applied to Perceptual Disorders Johannesburg September 2019